Amino-functionalized polyhedral oligomeric silsesquioxane cross-linking system capable of being used for water-based paint

By crosslinking aminoPOSS with epoxy-functionalized polyacrylate microspheres in an aqueous phase, the problems of VOC emissions and water solubility of crosslinking agents in waterborne coatings are solved, resulting in high-performance, zero-VOC waterborne coatings suitable for industrial applications on various substrates.

CN121343313APending Publication Date: 2026-01-16BEIJING SINGULAR POTENTIAL ENERGY NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511773083.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-28
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Existing waterborne coatings rely on volatile film-forming aids during the film-forming process, resulting in VOC emissions. Furthermore, common crosslinking agents have issues with water solubility and reactivity, making it difficult to achieve truly zero VOC addition and high-performance coatings.

Method used

An amino-functionalized polyhedral oligomeric silsesquioxane (NPOSS) and epoxy-functionalized polyacrylate polymer microspheres undergo an amine-epoxy addition reaction in an aqueous phase to form a cross-linked curing system. This avoids the need for additional organic solvents and film-forming aids. Cationic emulsifiers are used to construct core-shell structured microspheres to improve reaction efficiency and coating stability.

Benefits of technology

It enables the formation of a transparent and dense coating under low VOC conditions, improving the coating's heat resistance, mechanical strength, and chemical stability. It is suitable for conventional water-based coating processes and exhibits excellent adhesion and appearance on metal and glass substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121343313A_ABST
    Figure CN121343313A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer materials and coatings, and relates to an amino POSS (Polyhedral Oligomeric Silsesquioxane) crosslinking system for a water-based coating. The system takes water as a continuous phase, and comprises a water-soluble amino functionalized polyhedral oligomeric silsesquioxane (NPOSS) and an epoxy functionalized polyacrylate polymer microsphere aqueous dispersion, additives belonging to volatile organic compounds (VOC), such as organic solvents and coalescing agents, are not additionally added into the system. When in use, NPOSS as a multifunctional cross-linking agent is subjected to amine-epoxy addition reaction with an epoxy functionalized polymer in a water phase, and a cross-linked thermosetting coating can be formed on the surface of a base material such as an aluminum material, glass and the like. Compared with an existing water-based paint technology, the technology has the advantage that VOC emission in the film forming process of the water-based paint is remarkably reduced. Meanwhile, the NPOSS endows the coating with excellent thermal stability, mechanical strength and chemical resistance. The curing strategy is completely water-based, simple and convenient in process, environment-friendly and suitable for various fields with environmental protection requirements such as home furnishing, automobiles, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials and coatings technology. Specifically, it relates to a water-soluble amino-functionalized polyhedral oligomeric silsesquioxane crosslinking system for water-based coatings and its curing method. Background Technology

[0002] Coatings play an irreplaceable and crucial role in industries such as automotive, aerospace, construction, and electronics. They not only impart a decorative appearance to the substrate but also provide essential protective properties against mechanical wear, chemical corrosion, and environmental aging. For a long time, solvent-based coatings have dominated the market due to their excellent film-forming ability and application stability. However, their formulations often contain large amounts of volatile organic compounds (VOCs). During the coating and curing process, VOCs are continuously released into the atmosphere, causing serious environmental pollution and health risks. Therefore, promoting VOC emission reduction has become one of the core objectives of coating technology upgrades (Chin.J. Chem. Eng., 2022, 30 (5): 1234–1245.).

[0003] Waterborne coatings are widely regarded as an ideal alternative due to their environmental advantages, such as low toxicity, non-flammability, and low VOC content. However, most waterborne systems still rely on film-forming aids to lower the minimum film-forming temperature and promote the aggregation and film formation of emulsion particles. Although these small-molecule organic compounds play a role in the film-forming stage, they are VOCs and will eventually evaporate, which to some extent weakens the environmental advantages of waterborne coatings (Atmosphere, 2023, 14 (4):662.). This dependence on volatile additives makes it difficult to achieve truly zero-VOC coatings in actual industrialization.

[0004] To further enhance the density of coatings and impart superior thermal stability, mechanical strength, and chemical resistance, chemical crosslinking technology is often introduced in industry. Common crosslinking agents include polyisocyanates, amines, carboxylic acids, polyols, and silanes. However, these crosslinking agents generally suffer from poor water solubility or easy reaction with water. To overcome these problems, organic solvents are often added to the curing agent, further increasing the VOC content in waterborne coatings. In addition, most waterborne crosslinking systems still require film-forming aids to achieve initial film formation, followed by final curing through a crosslinking reaction, without fundamentally removing volatile components (RSC Sustainability, 2024, 2: 3704–3729.).

[0005] In conclusion, developing a waterborne coating crosslinking technology that does not require the addition of any organic solvents or film-forming aids has significant practical implications and application value. Summary of the Invention

[0006] The purpose of this invention is to provide a system and method for achieving crosslinking and curing in an aqueous medium by undergoing an amine-epoxy addition reaction between an amino-functionalized polyhedral oligomeric silsesquioxane and an epoxy-functionalized polyacrylate polymer microsphere aqueous dispersion. This results in a transparent and dense coating without the addition of organic solvents and film-forming aids, and achieves a synergistic improvement in heat resistance, mechanical strength, and chemical resistance with a relatively low POSS addition amount.

[0007] Another object of the present invention is to provide a method for preparing the polymer and curing agent involved in the above-mentioned aqueous crosslinking system, wherein the method is mild, the raw materials are readily available, and it is suitable for scale-up and industrial implementation.

[0008] Another objective of this invention is to provide a water-based coating and its molding method prepared based on the above-mentioned polymer and curing agent. This coating is compatible with conventional water-based coating processes (spraying, brushing, curtain coating, etc.) and can form a cross-linked thermosetting coating with excellent adhesion and appearance on substrates such as metals (e.g., aluminum and aluminum alloys) and glass.

[0009] In a first aspect, the present invention provides an amino POSS crosslinking system for waterborne coatings with zero VOC addition.

[0010] The system uses water as the continuous phase and contains an aqueous dispersion of amino-functionalized polyhedral oligomeric silsesquioxane (NPOSS) and epoxy-functionalized polyacrylate polymer microspheres that are soluble or stably dispersed in the aqueous phase. The system is cured and shaped by an amine-epoxy addition reaction, wherein "zero VOC addition" means that no additional organic solvents and film-forming aids are added to the formulation.

[0011] Preferably, the POSS can be expressed in the general formula [RSiO]. 1.5 ] n The expression indicates that n is 6-14, including a complete cage-like or partially open cage structure; R is an organic substituent, wherein at least two R groups contain at least one amino or protonated amino functional group; more preferably, n is 8 (T8), and the POSS is octa(3-aminopropyl)-POSS.

[0012] Preferably, the epoxy-functionalized polyacrylate polymer microsphere aqueous dispersion is prepared by seed emulsion polymerization, and epoxy functional groups are introduced into its polymer backbone or side chains.

[0013] Secondly, the present invention provides a method for preparing the above-mentioned epoxy-functionalized polyacrylate polymer microsphere aqueous dispersion, comprising the following steps:

[0014] A monomer preemulsion A is prepared by adding a portion of surfactant and monomer to water and stirring. A monomer preemulsion B is prepared by adding another portion of surfactant and monomer to water and stirring. A portion of the initiator is prepared into a 3%-5% solution C using deionized water. A portion of the surfactant is prepared into a solution D using deionized water. A portion of the initiator is prepared into a 2%-3% solution E using deionized water.

[0015] Reaction process: Solution D was added to a jacketed glass reactor equipped with a condenser, thermometer, and stirrer. After nitrogen purging, the reaction temperature was raised to 85 °C, and stirring was started. 10% by mass of monomer preemulsion A was added to the reactor as a seed, and after stirring for 3-5 min, solution C was added. Stirring continued for 20-30 min. Then, monomer preemulsion A and solution E were added dropwise simultaneously. The remaining monomer preemulsion A was added uniformly using a peristaltic pump over 1.5 h, and solution E was added uniformly using a syringe pump over 1.5 h. After the addition was complete, the reaction was kept at the temperature for 1 h. Then, monomer preemulsion B and solution E were added dropwise simultaneously. The remaining monomer preemulsion B was added uniformly using a peristaltic pump over 1.5 h, and solution E was added uniformly using a syringe pump over 1.5 h. After the addition was complete, the reaction was kept at the temperature for 1 h. The reaction temperature was lowered to 40 °C, and the reaction solution was filtered through a 200-mesh filter to obtain an aqueous dispersion of epoxy-functionalized polyacrylate microspheres.

[0016] Preferably, the monomer used in the preparation of the epoxy-functionalized polyacrylate polymer microsphere aqueous dispersion may be one or more of styrene, acrylic acid and acrylate monomers, methacrylic acid and methacrylate monomers, and olefin-containing glycidyl ester monomers; more preferably, it may be one or more of styrene, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, butyl methacrylate, hydroxyethyl methacrylate, β-hydroxypropyl methacrylate, glycidyl methacrylate, and isobornyl methacrylate; most preferably, the monomer may be one or more of methyl methacrylate, 2-ethylhexyl acrylate, glycidyl methacrylate, and isobornyl methacrylate.

[0017] Preferably, the initiator used in the preparation of the epoxy-functionalized polyacrylate microsphere dispersion can be a peroxide, persulfate, or azo initiator; more preferably, it can be benzoyl peroxide, di-tert-butyl peroxide, potassium persulfate, sodium persulfate, ammonium persulfate, azobisisobutyronitrile, azobisisoheptanenitrile, or azobisisobutyramidine hydrochloride; most preferably, the initiator is azobisisobutyronitrile or azobisisobutyramidine hydrochloride.

[0018] Preferably, the surfactant used in the preparation of the epoxy-functionalized polyacrylate microsphere dispersion can be anionic surfactant, cationic surfactant, and / or nonionic surfactant, such as sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, octadecyltrimethylammonium bromide, didodecyl dimethylammonium chloride, sorbitan monostearate, polysorbate-60, polyoxyethylene laurate, cetearyl alcohol polyether-20, nonylphenol polyoxyethylene ether, and reactive surfactant ER-30 (Adico Corporation, Japan); more preferably, it can be one, two, or three of tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide, or ER-30.

[0019] Preferably, the monomer to water ratio (W / W) used in the preparation of the epoxy-functionalized polyacrylate microsphere dispersion can be 1:0.5 - 1:2, such as 1:0.5, 1:0.8, 1:1, 1:1.2, 1:1.5, 1:1.8, or 1:2, etc. More preferably, the monomer to water ratio is 1:1.5 - 1:1.8. The weight (W) is calculated in grams (g).

[0020] Preferably, the ratio (w / w) of the initiator to the monomer used in the preparation of the epoxy-functionalized polyacrylate microsphere dispersion is 0.1% - 1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; more preferably, the ratio is 0.3% - 0.5%. The weight (w) is calculated in grams (g).

[0021] Preferably, the reaction temperature used in the preparation of the epoxy-functionalized polyacrylate microsphere dispersion can be 40 ℃, 45 ℃, 50 ℃, 55 ℃, 60 ℃, 65 ℃, 70 ℃, 75 ℃, 80 ℃, 85 ℃ or 90 ℃; more preferably, the reaction temperature can be 70 ℃, 75 ℃, 80 ℃, 85 ℃ or 90 ℃; most preferably, the reaction temperature can be 85 ℃.

[0022] Preferably, the stirring method can be mechanical stirring, with a speed of 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 900 rpm, 1000 rpm, 1250 rpm, or 1500 rpm; more preferably, the stirring speed is 300 rpm.

[0023] Thirdly, the present invention provides a method for preparing and molding waterborne coatings based on the above-mentioned curing method and polymer dispersion, wherein leveling agents, defoamers, wetting agents, thickeners and other additives may or may not be added to the formulation.

[0024] Preferably, the POSS aqueous solution and the epoxy-functionalized polyacrylate microsphere dispersion are uniformly mixed in the aqueous phase to obtain a curable composition. After being applied to the surface of a pretreated substrate, the composition is cured into a film by amine-epoxy addition under room temperature or heating conditions.

[0025] Preferably, the amine-epoxy equivalent ratio in the crosslinking formulation is 0.5:1 – 3:1.

[0026] Preferably, the curing temperature is 20-150℃, such as 20℃, 30℃, 40℃, 60℃, 80℃, 100℃, 120℃, 140℃, or 150℃.

[0027] The present invention has the following advantages over the prior art:

[0028] First, an amino POSS crosslinking system was invented that can be used in water-based coatings, which can be used to develop new water-based coating formulations that do not require the addition of VOC additives, thus helping to reduce VOC emissions during the coating process.

[0029] Secondly, a composite emulsification system of cationic and nonionic emulsifiers was selected, and a core-shell structured polymer microsphere aqueous dispersion was constructed through seed emulsion polymerization. This design directionally enriches reactive epoxy groups in the microsphere shell, providing sufficient sites for efficient crosslinking with amino POSS; at the same time, while ensuring polymerization and storage stability, the cationic components in this composite emulsification system also synergistically endow the coating with antibacterial properties, achieving integration from structural design to function.

[0030] Third, the amino-POSS crosslinking system can form high-performance POSS-polymer composites while curing the polymer. Compared with polymer materials, POSS-polymer composites have the advantages of good heat resistance, high mechanical strength, and strong solvent resistance.

[0031] Fourth, epoxy-functionalized polyacrylate microsphere dispersions and water-soluble amino POSS can be directly formulated in the aqueous phase, resulting in stable dispersion, simple process, controllable activation period, and compatibility with common water-based coating processes such as spraying. This facilitates scale-up and is well-suited for industrial coating processes such as spraying.

[0032] Fifth, the amino POSS crosslinking system of water-based coatings has strong adhesion, uniform surface, and high transparency on substrates such as aluminum and glass, and has application potential and economic value in scenarios such as home furnishing, automobiles, aerospace, construction and electronic coating. Attached Figure Description

[0033] Figure 1 This is a comparison chart of DSC curves for amino POSS crosslinked cured materials.

[0034] Figure 2 This is a comparison chart of TGA curves for amino POSS crosslinked cured materials.

[0035] Figure 3 This is a comparison chart of stress-strain curves of aminoPOSS cross-linked cured materials. Detailed Implementation

[0036] The following are preferred embodiments of the present invention to further explain the advantages of the present invention. However, the following description is only for explaining the present invention and does not limit its content.

[0037] Example 1: Preparation of an epoxy-functionalized core-shell polyacrylate microsphere aqueous dispersion

[0038] Add 0.27 g cetyltrimethylammonium bromide (CTAB) and 0.52 g ER-30 to 33.5 g deionized water, then add 21.03 g methyl methacrylate and 12.08 g 2-ethylhexyl acrylate sequentially, and stir at 1500 rpm for 3 h to obtain a stable monomer preemulsion A.

[0039] Add 0.27 g CTAB and 0.52 g ER-30 to 33.5 g deionized water, then add 18.11 g methyl methacrylate, 8.96 g 2-ethylhexyl acrylate and 6.04 g glycidyl methacrylate in sequence, and stir at 1500 rpm for 3 h to obtain a stable monomer preemulsion B.

[0040] Prepare solution C by dissolving 0.10 g of initiator azobisisobutyramidine hydrochloride in 5.00 g of deionized water;

[0041] Prepare solution D by dissolving 0.10 g of initiator azobisisobutyramidine hydrochloride in 5.00 g of deionized water;

[0042] In a 1 L jacketed glass reactor equipped with a condenser, thermometer, and stirrer, 0.30 g of CTAB and 0.25 g of ER-30 were added. After purging with nitrogen, the reaction temperature was raised to 85 °C, and stirring was started (D = 40 mm, 300 rpm). 10% by mass of monomer preemulsion A was added as a seed to the reactor, and after stirring for 3-5 min, solution B was added. The reaction was continued at 85 °C for 20 min. Then, monomer preemulsion A and solution C were added dropwise simultaneously. Over 1.5 h, the remaining monomer preemulsion A and solution D were added at a uniform rate. After the addition was complete, the reaction was maintained at this temperature for 1 h. Then, monomer preemulsion B and solution D were added dropwise simultaneously at a uniform rate over 1.5 h. After the addition was complete, the reaction was maintained at this temperature for 1 h. The reaction temperature was lowered to 40 °C, and the mixture was filtered through a 200-mesh screen to obtain epoxy-functionalized core-shell polyacrylate microsphere aqueous dispersion PM-1. PM-1 was freeze-dried using a vacuum freeze dryer to obtain PM-1 freeze-dried particles.

[0043] The obtained epoxy-functionalized core-shell polyacrylate microsphere dispersion PM-1 has the following basic properties:

[0044] The product has a milky white appearance with a bluish tint, a yield of 96.49%, and a solids content of 37.66%.

[0045] The particle size and zeta potential of PM-1 were analyzed using a nanoparticle size and zeta potential analyzer. The average particle size was 107.91 nm, the polydispersity index (PDI) was 0.058, and the zeta potential was 44.1 mV.

[0046] Example 2: Preparation of an epoxy-functionalized core-shell polyacrylate microsphere aqueous dispersion

[0047] Add 0.27 g cetyltrimethylammonium bromide (CTAB) and 0.52 g ER-30 to 33.5 g deionized water, then add 7.94 g methyl methacrylate and 25.45 g 2-ethylhexyl acrylate sequentially, and stir at 1500 rpm for 3 h to obtain a stable monomer preemulsion A;

[0048] Add 0.27 g CTAB and 0.52 g ER-30 to 33.5 g deionized water, then add 18.11 g methyl methacrylate, 8.96 g 2-ethylhexyl acrylate and 6.04 g glycidyl methacrylate in sequence, and stir at 1500 rpm for 3 h to obtain a stable monomer preemulsion B.

[0049] Prepare solution C by dissolving 0.10 g of initiator azobisisobutyramidine hydrochloride in 5.00 g of deionized water;

[0050] Prepare solution D by dissolving 0.10 g of initiator azobisisobutyramidine hydrochloride in 5.00 g of deionized water;

[0051] In a 1 L jacketed glass reactor equipped with a condenser, thermometer, and stirrer, 0.30 g of CTAB and 0.25 g of ER-30 were added. After purging with nitrogen, the reaction temperature was raised to 85 °C, and stirring was started (D = 40 mm, 300 rpm). 10% by mass of monomer preemulsion A was added as a seed to the reactor, and after stirring for 3-5 min, solution B was added. The reaction was continued at 85 °C for 20 min. Then, monomer preemulsion A and solution C were added dropwise simultaneously. The remaining monomer preemulsion A and solution D were added uniformly over 1.5 h. After the addition was complete, the reaction was maintained at this temperature for 1 h. Then, monomer preemulsion B and solution D were added dropwise uniformly over 1.5 h. After the addition was complete, the reaction was maintained at this temperature for 1 h. The reaction temperature was lowered to 40 °C, and the mixture was filtered through a 200-mesh screen to obtain an epoxy-functionalized core-shell polyacrylate microsphere aqueous dispersion PM-2. PM-2 was freeze-dried using a vacuum freeze dryer to obtain PM-2 freeze-dried particles.

[0052] The obtained epoxy-functionalized core-shell polyacrylate microsphere dispersion PM-2 has the following basic properties:

[0053] The product has a milky white appearance with a bluish tint, a yield of 96.97%, and a solids content of 37.85%.

[0054] The particle size and zeta potential of PM-2 were analyzed using a nanoparticle size and zeta potential analyzer. The average particle size was 108.30 nm, the polydispersity index (PDI) was 0.041, and the zeta potential was 40.5 mV.

[0055] Example 3: Preparation of an epoxy-functionalized core-shell polyacrylate microsphere aqueous dispersion

[0056] Add 0.27 g tetradecyltrimethylammonium bromide (TTAB) and 0.52 g ER-30 to 33.5 g deionized water, then add 11.06 g methyl methacrylate and 22.05 g 2-ethylhexyl acrylate sequentially, and stir at 1500 rpm for 3 h to obtain a stable monomer preemulsion A;

[0057] Add 0.27 g TTAB and 0.52 g ER-30 to 33.5 g deionized water, then add 18.11 g methyl methacrylate, 8.96 g 2-ethylhexyl acrylate, 6.04 g glycidyl methacrylate and 6.62 g isobornyl methacrylate in sequence, and stir at 1500 rpm for 3 h to obtain a stable monomer preemulsion B;

[0058] Prepare solution C by dissolving 0.10 g of initiator azobisisobutyramidine hydrochloride in 5.00 g of deionized water;

[0059] Prepare solution D by dissolving 0.10 g of initiator azobisisobutyramidine hydrochloride in 5.00 g of deionized water;

[0060] In a 1 L jacketed glass reactor equipped with a condenser, thermometer, and stirrer, 0.30 g of TTAB and 0.25 g of ER-30 were added. After purging with nitrogen, the reaction temperature was raised to 85 °C, and stirring was started (D = 40 mm, 300 rpm). 10% by mass of monomer preemulsion A was added as a seed to the reactor, and after stirring for 3-5 min, solution B was added. The reaction was continued at 85 °C for 20 min. Then, monomer preemulsion A and solution C were added dropwise simultaneously. Over 1.5 h, the remaining monomer preemulsion A and solution D were added at a uniform rate. After the addition was complete, the reaction was maintained at this temperature for 1 h. Then, monomer preemulsion B and solution D were added dropwise simultaneously at a uniform rate over 1.5 h. After the addition was complete, the reaction was maintained at this temperature for 1 h. The reaction temperature was lowered to 40 °C, and the mixture was filtered through a 200-mesh screen to obtain an epoxy-functionalized core-shell polyacrylate microsphere aqueous dispersion PM-3. PM-3 was freeze-dried using a vacuum freeze dryer to obtain PM-3 freeze-dried particles.

[0061] The obtained epoxy-functionalized core-shell polyacrylate microsphere dispersion PM-3 has the following basic properties:

[0062] The product has a milky white appearance with a bluish tint, a yield of 97.10%, and a solids content of 37.97%.

[0063] The particle size and zeta potential of PM-3 were analyzed using a nanoparticle size and zeta potential analyzer. The average particle size was 98.05 nm, the polydispersity index (PDI) was 0.021, and the zeta potential was 34.5 mV.

[0064] Example 4: Preparation of octa(3-aminopropyl)-POS

[0065] Octa(3-aminopropyl)octasilsesquioxane (CAS: 150380-11-3, NPOSS) was synthesized by the following method: (3-aminopropyl)triethoxysilane (15 mL, 60 mmol) was dissolved in concentrated hydrochloric acid (37%, 30 mL) in methanol (350 mL), and the mixture was maintained at 90 °C for 18 hours. After cooling to room temperature, the result was poured into 200 mL of THF, resulting in a white precipitate. The crude product was then thoroughly washed with cold methanol and subsequently dried under reduced pressure to give a white solid NPOSS (2.81 g, yield 30%). Due to the acidic conditions, the product was in the ammonium salt form of NPOSS.

[0066] By nuclear magnetic resonance hydrogen spectrum ( 1 H NMR, carbon spectrum ( 13 C NMR, silicon spectroscopy (C NMR), 29 The structure of NPOSS was confirmed by Si NMR and high-resolution mass spectrometry (HRMS).

[0067] 1 H NMR (500 MHz, DMSO-d6): δ 8.25 (s, 24H), 2.78 (m, 16H), 1.73 (m, 16H), 0.74 (m, 16H);

[0068] 13 C{ 1 H} NMR (126 MHz, DMSO-d6): δ 41.00, 20.59, 8.42;

[0069] 29 Si NMR (400 MHz, DMSO-d6): δ – 66.5 (s);

[0070] HRMS (m / z, [M+H]+): 881.2876 (calculated value), 881.2883 (measured value).

[0071] Example 5: Construction of an epoxy-functionalized polyacrylate microsphere aqueous dispersion crosslinking system based on aminoPOSS and preparation of its cured material

[0072] The NPOSS described in Example 4 was dissolved in deionized water to obtain an aqueous solution of 31.6 mg / mL.

[0073] Using the products obtained in Examples 1, 2 and 3 as raw materials, the curing agent solution and the epoxy-functionalized polyacrylate microsphere aqueous dispersion were mixed in an amine to epoxy equivalent ratio of 2:1 to obtain an epoxy-functionalized polyacrylate microsphere aqueous dispersion crosslinking system based on amino POSS. The resulting formulations are denoted as PA-1, PA-2 and PA-3, respectively.

[0074] 1.5 mL of the obtained formulation was sprayed into a pre-cleaned dumbbell-shaped polytetrafluoroethylene (PTFE) mold (size: 50 mm × 10 mm × 1 mm). The mold surface was dry, oil-free, and dust-free. Subsequently, the material corresponding to formulation PA-1 was heat-cured in an oven at 100°C for 48 h to form a uniform and transparent cross-linked material CA-1; the material corresponding to formulation PA-2 was cured at 50°C for 48 h to form a uniform and transparent cross-linked material CA-2.

[0075] The curing agent solution was mixed with the epoxy-functionalized polyacrylate microsphere aqueous dispersion PM-3 at a 2:1 amine-to-epoxy equivalent ratio to obtain an amino-POSS-based epoxy-functionalized polyacrylate microsphere aqueous dispersion crosslinking system. The obtained PA-3 formulation was sprayed onto pre-cleaned aluminum substrates (70 mm × 150 mm × 0.5 mm) and glass substrates (297 mm × 420 mm × 10 mm), ensuring the surfaces were dry, oil-free, and dust-free. Subsequently, it was heat-cured in an oven at 120°C for 48 h to form uniform, transparent crosslinked coatings CA-3 (aluminum substrate surface) and CA-4 (glass substrate surface).

[0076] Comparative Example 6: Construction of a crosslinking system for epoxy-functionalized polyacrylate microspheres based on polyetheramine and preparation of its cured material

[0077] The amino-terminated polyether ZT-143 was dissolved in deionized water to obtain an aqueous solution of 37.15 mg / mL.

[0078] Using the products obtained in Examples 1, 2 and 3 as raw materials, the curing agent solution and the epoxy-functionalized polyacrylate microsphere aqueous dispersion were mixed in an amine to epoxy equivalent ratio of 2:1 to obtain an epoxy-functionalized polyacrylate microsphere aqueous dispersion crosslinking system based on terminal amino polyether ZT-143. The resulting formulations are denoted as PB-1, PB-2 and PB-3, respectively.

[0079] 1.5 mL of the obtained formulation was sprayed into a pre-cleaned dumbbell-shaped polytetrafluoroethylene (PTFE) mold (size: 50 mm × 10 mm × 1 mm). The mold surface was dry, oil-free, and dust-free. Subsequently, the material corresponding to formulation PB-1 was heat-cured in an oven at 100°C for 48 h to form a uniform and transparent cross-linked material CB-1; the material corresponding to formulation PB-2 was cured at 50°C for 48 h to form a uniform and transparent cross-linked material CB-2.

[0080] The curing agent solution was mixed with the epoxy-functionalized polyacrylate microsphere aqueous dispersion PM-3 at a 2:1 amine-to-epoxy equivalent ratio to obtain an amino-POSS-based epoxy-functionalized polyacrylate microsphere aqueous dispersion crosslinking system. The obtained formulation PB-3 was sprayed onto pre-cleaned aluminum substrates (70 mm × 150 mm × 0.5 mm) and glass substrates (297 mm × 420 mm × 10 mm), ensuring the surfaces were dry, oil-free, and dust-free. Subsequently, it was heat-cured in an oven at 120°C for 48 h to form uniform, transparent crosslinked coatings CB-3 (aluminum substrate surface) and CB-4 (glass substrate surface).

[0081] Comparative Example 7: Preparation of Cured Materials Based on Epoxy-Functionalized Polyacrylate Microsphere Aqueous Dispersions

[0082] Using the products obtained in Examples 1 and 2 as raw materials, deionized water was added at a mass ratio of 1:1 without adding any additional curing agent solution to obtain an epoxy-functionalized polyacrylate microsphere aqueous dispersion crosslinking system without curing agent addition. The resulting formulations are denoted as PC-1 and PC-2, respectively.

[0083] 1.5 mL of the obtained formulation was sprayed into a pre-cleaned dumbbell-shaped polytetrafluoroethylene (PTFE) mold (size: 50 mm × 10 mm × 1 mm). The mold surface was dry, oil-free, and dust-free. Subsequently, the material corresponding to formulation PC-1 was heat-cured in an oven at 100°C for 48 h to form a uniform and transparent crosslinked material CC-1; the material corresponding to formulation PC-2 was cured at 50°C for 48 h to form a uniform and transparent crosslinked material CC-2.

[0084] Example 8: Characterization and Comparison of Thermal Properties of Amino POSS Crosslinked Cured Materials

[0085] The thermal properties of the cured materials CA-1, CB-1 and CC-1 obtained in Example 5, Comparative Example 6 and Comparative Example 7 were tested.

[0086] Differential scanning calorimetry (DSC) was performed using a TA Q200 instrument to evaluate the thermal transition of the crosslinked material. Approximately 5.0 mg of each dumbbell-shaped sample was sealed in an aluminum crucible and heated from -50 °C to 200 °C at a rate of 10 °C / min under a nitrogen atmosphere.

[0087] Thermogravimetric analysis (TGA) was performed on a Netzsch STA 449 F5 instrument to assess thermal stability. Approximately 10.0 mg of each dumbbell-shaped sample was placed in an aluminum crucible and heated from room temperature to 800 °C at a rate of 10 °C / min under a nitrogen flow. The onset of thermal degradation was determined by the inflection point (maximum slope) of the TGA curve, and the temperature at which 5% weight loss occurred (T5%) was reported as the thermal degradation threshold.

[0088] Table 1. Comparison of thermal properties of cured materials CA-1, CB-1 and CC-1

[0089]

[0090] Test data is attached. Figure 1 Appendix Figure 2 As shown in Table 1, the data indicates that the amino-POSS crosslinked cured material CA-1 prepared by the method described in this patent exhibits the best overall thermal properties. Its glass transition temperature (Tg) reaches 40.01 °C, which is significantly improved compared to comparative examples CB-1 (35.48 °C) and CC-1 (38.20 °C). This suggests that the introduction of the POSS nanocage structure enhances the rigidity and dimensional stability of the material.

[0091] More importantly, the thermal stability of material CA-1 was significantly enhanced, with an initial decomposition temperature (T5%) reaching 303.5 °C. This represents an increase of approximately 7.5 °C compared to CB-1 (296.0 °C), and a substantial increase of nearly 30 °C compared to CC-1 (274.0 °C). This result fully demonstrates that the crosslinking effect of amino POSS significantly improves the thermal degradation threshold of the material, endowing the cured material with superior thermal stability and heat resistance, and broadening its application potential in high-temperature environments.

[0092] Example 9: Characterization and Comparison of Mechanical Properties of Amino POSS Crosslinked Cured Materials

[0093] Mechanical properties of the cured materials CA-2 and CB-2 obtained in Example 5 and Comparative Example 6 were tested. Static mechanical property tests were conducted using a Shimadzu AGS-X-50N electronic universal testing machine. Tests were carried out in a constant temperature and humidity laboratory environment (temperature: 25 ± 2 ℃, relative humidity: 50 ± 5%). Specific test parameters are as follows:

[0094] Fixture type: pneumatic flat-push fixture with a toothed surface with a specified pattern to ensure that the sample does not slip during the test.

[0095] Gauge length: The gauge length (typically 25 mm) is precisely measured using a non-contact video extensometer to accurately record the true strain of the specimen.

[0096] Tensile rate: set to 10 mm / min until the sample completely breaks.

[0097] Data Acquisition: The testing machine system acquires load (N) and displacement (mm) data synchronously in real time at a high frequency (≥50 Hz) and automatically calculates and generates stress (MPa)-strain (%) curves. Each measurement is repeated three times to ensure repeatability.

[0098] Typical stress-strain curves are shown in the attached figure. Figure 3 As shown, the quantitative test data are summarized in the table below.

[0099] Table 2 Comparison of mechanical properties of cured materials CA-2 and CB-2

[0100]

[0101] Data shows that CA-2, cured with POSS, exhibits 159.9% higher elongation at break, 163.0% higher tensile strength, and 32.7% higher elastic modulus compared to the comparative CB-2. This indicates that the introduction of POSS as a crosslinking agent significantly enhances material strength without sacrificing toughness; on the contrary, it endows the material with excellent ductility and flexibility.

[0102] In summary, the mechanical property test data fully demonstrate that, compared with conventional techniques in the field (Comparative Example CB-2), the cured material (Example CA-2) prepared using the amino POSS described in this invention as a crosslinking agent achieves simultaneous and significant improvements in key mechanical properties such as tensile strength, elongation at break, and elastic modulus, fully reflecting the outstanding substantive features and significant technological progress of this invention.

[0103] Example 10: Performance Testing and Comparison of Amino POSS Crosslinked Coatings

[0104] The performance of the crosslinked coatings of the cured materials CA-3, CB-3 and CA-4, CB-4 obtained in Example 5 and Comparative Example 6 were tested and compared.

[0105] The thickness of the cross-linked coating was measured using a magnetically inductive coating thickness gauge. Tests were conducted on an aluminum substrate (70 mm × 150 mm × 0.5 mm), first calibrated against an uncoated reference panel. Measurements were then taken at five random locations at least 10 mm from the edge of the sample, and the average value was recorded.

[0106] Pencil hardness was measured according to ISO 15184:2020 standard using a standard pencil hardness tester (Zhonghua Pencil). Coated aluminum plates CA-3 and CB-3 were placed horizontally and tested at a fixed angle and with a fixed force. The highest pencil grade that did not produce continuous scratches exceeding 3 mm was recorded, and the measurement was repeated three times.

[0107] Coating adhesion was evaluated using a cross-cutting method according to ISO 2409:2020. A grid cut was performed on coated aluminum plates CA-3 and CB-3 using a BGD503 multi-blade cutter (Biaogeda, China), with a blade spacing of 1 mm. Standardized tape of 75 mm width was firmly applied to the cut area and quickly peeled off. The degree of coating peeling was evaluated at magnification according to the standard rating criteria. The test was repeated three times.

[0108] Scratch resistance was evaluated using a BGD 5202 electric scratch tester (Biuged) according to ISO 1518-2:2011. Test samples were coated aluminum plates CA-3 and CB-3. A hemispherical tungsten carbide probe with a diameter of 1.0 mm was used. A fixed normal load was applied, gradually increasing from 0.5 N to 10.0 N. After testing, the scratches were examined under an optical microscope at 40 × magnification. The critical load Fc was defined as the lowest normal force at which the coating exhibited significant failure (e.g., cracking, delamination, or penetration into the substrate). The value of Fc was determined by correlating the failure location along the scratch path with the corresponding load using the calibration scale on the instrument. The experiment was repeated three times to ensure repeatability.

[0109] Impact resistance was tested using a BGD 301 impact testing machine (Biuged) according to ISO 6272-2:2011. Coated aluminum plates CA-3 and CB-3 were mounted horizontally with the coated surface facing upwards. Using a hemispherical impactor (12.7 ± 0.1 mm in diameter) and a 1000-gram drop weight, five consecutive impacts were performed at each height. Damage to the affected area was then examined at 4 × 10⁻⁶ magnification. The maximum impact energy that did not cause observable cracking, wrinkling, or delamination was reported in Joules (J).

[0110] The transmittance of the coating was analyzed using an LS183 transmittance meter (Linshang). Coated glass panels CA-4 and CB-4 (297 mm × 420 mm × 10 mm) were compared with uncoated glass. Transmittance values ​​were measured in the ultraviolet (UV), infrared (IR), and visible (VL) regions. Three locations were randomly selected for measurement on each panel, and the average value was reported.

[0111] Gloss was measured using a gloss meter at an incident angle of 20°, according to ISO 2813:2014. The instrument was calibrated with a standard black glass brick before use. For each sample, three points were selected on the surface of the coated aluminum plate CA-3 and CB-3 for measurement, and the measurements were repeated three times. The gloss values ​​were then calculated.

[0112] According to ISO 2812-4:2017, coated aluminum plates CA-3 and CB-3 were exposed to a range of chemicals, including distilled water, boiling water, ethanol (95% and 50%), hydrochloric acid (10% solution in deionized water), sodium hydroxide (5% solution in deionized water), and diesel oil. For each chemical, 0.1 mL of the solution was applied to the coated aluminum surface and covered with a glass petri dish. After 1 hour or 24 hours of exposure, the chemicals were removed using a lint-free nonwoven fabric. The water-treated samples were rinsed with deionized water and dried. The surface was visually inspected under ambient light for any signs of discoloration, blistering, swelling, or delamination. After standing at room temperature for another 1 hour or 24 hours, the coating was reassessed to determine any delayed degradation effects.

[0113] Rating Methodology:

[0114] Grade 0: Under the specified observation conditions, no changes are visible on the coating surface. Gloss, color, and texture are completely consistent with the untested area.

[0115] Level 1: The coating surface exhibits extremely subtle changes that require very close inspection to observe. For example, very slight loss of gloss or color variation that is only visible at specific angles. Its protective performance is generally considered unaffected.

[0116] Level 2: The change is noticeable but mild. For example: clear loss of gloss, slight softening, or minor discoloration. The change remains after wiping with a cloth, but there is no structural damage such as bubbling or cracking.

[0117] Level 3: The coating exhibits significant and permanent defects. Examples include noticeable discoloration, loss of gloss, wrinkling, or the presence of a small number of fine bubbles. The decorative and protective properties of the coating have been significantly reduced.

[0118] Level 4: The coating shows severe damage. Examples include dense blistering, noticeable cracking, peeling, or swelling. Liquid may have penetrated the substrate, causing localized substrate exposure. The coating has essentially lost its protective function.

[0119] Level 5: The coating is completely or extensively damaged. Large areas of peeling and flaking occur, completely exposing the substrate. The coating can no longer adhere to the substrate, and its protective and decorative functions are completely lost.

[0120] Table 3 Comparison of coating performance between curing materials CA-3 and CB-3

[0121]

[0122] The coating performance was tested according to the above testing methods. The thickness of all tested coatings was precisely controlled to approximately 11 μm to ensure fair comparison. Performance test results show that CA-3, cured via POSS crosslinking, exhibits comprehensive and significant performance advantages. Its pencil hardness reached 2H, two levels higher than the comparative CB-3, demonstrating higher surface stiffness and scratch resistance. Simultaneously, CA-3 showed excellent adhesion to aluminum surfaces, achieving the highest standard of Grade 0.

[0123] In terms of scratch resistance, the improvement of CA-3 material is particularly outstanding, increasing by 247.4% compared to CB-3, indicating that it can withstand more severe mechanical wear. In addition, its surface optical properties have also been greatly improved, with a significant increase of 76.4% in 20° specular gloss, significantly enhancing the appearance and texture of the products.

[0124] Table 4 Comparison of light transmittance properties of coatings made of cured materials CA-2 and CB-2

[0125]

[0126] More importantly, while achieving these superior properties, the coating still maintains excellent optical transparency, with minimal change in transmittance compared to the uncoated substrate, fully demonstrating that the POSS crosslinking structure does not sacrifice transparency while endowing the coating with functionality.

[0127] Table 5. Comparison of chemical resistance properties of coatings made of curing materials CA-2 and CB-2

[0128]

[0129] In terms of chemical resistance, CA-3 exhibited excellent resistance to all solvents tested, achieving grades 0 or 1. Particularly in acid and alkali resistance, it showed improvements of 4 and 5 grades respectively compared to CB-3, demonstrating outstanding potential for protection against acid and alkali corrosion.

[0130] In summary, the data from this embodiment fully demonstrate that material CA-3, cured with an amino POSS crosslinking agent, achieves significant improvements over CB-3 in several key indicators, including mechanical properties, optical properties, and chemical stability. Achieving this synergistic and efficient improvement in hardness, adhesion, scratch resistance, gloss, transparency, and solvent resistance with zero VOC addition reflects the prominent substantive features and significant technological advancements of this invention.

Claims

1. An amino-functionalized polyhedral oligomeric silsesquioxane crosslinking system, characterized in that: an amino-functionalized polyhedral oligomeric silsesquioxane is used as a crosslinking agent for the curing reaction of an epoxy-functionalized polyacrylate polymer.

2. The crosslinking system of claim 1, characterized in that: The amino-functionalized polyhedral oligomeric silsesquioxanes are cage silsesquioxane structures having the structure [RSiO 1.5 ] n wherein n is 6 - 14, R is an organic substituent, the n R groups can be the same or different, and wherein at least two of the R groups contain at least one amino or protonated amino functional group.

3. The crosslinking system of claim 1, characterized in that: the epoxy-functionalized polyacrylate polymer is a water dispersion of polymer microspheres.

4. The crosslinking system of claim 1, characterized in that: the system can realize the molding or film forming of polymer materials without the addition of organic solvents and film forming aids.

5. An aqueous coating formulation using the crosslinking system of claim 1, characterized in that: an aqueous solution of amino-functionalized polyhedral oligomeric silsesquioxane is mixed with a water dispersion of epoxy-functionalized polyacrylate polymer microspheres to obtain a curable aqueous coating formulation with or without the addition of aids.

6. A method for preparing a coating layer using the aqueous coating formulation of claim 5, characterized in that: the curable aqueous coating formulation is coated onto the surface of a substrate; the amino-functionalized polyhedral oligomeric silsesquioxane and the epoxy functional group undergo amine-epoxy addition reaction without the addition of organic solvents and film forming aids, and the curing is completed with or without heating to obtain a crosslinked thermoset coating layer.

7. A coating layer prepared using the method of claim 6, characterized in that: the coating layer is a transparent crosslinked thermoset coating layer, which exhibits excellent thermal stability, mechanical strength and chemical resistance, and good adhesion and surface uniformity on metal or glass substrates.

8. An epoxy-functionalized polyacrylate polymer microsphere water dispersion and a method for preparing the same, characterized in that: a seed emulsion polymerization process is used; first step, preparing a core monomer pre-emulsion: water, emulsifier, and a core monomer mixture are emulsified to form a core monomer pre-emulsion; the emulsifier is a complex emulsifying system of cationic emulsifier and non-ionic emulsifier, and the core monomer mixture contains acrylate monomers; second step, preparing a shell monomer pre-emulsion: water, emulsifier, and a shell monomer mixture are emulsified to form a shell monomer pre-emulsion; the emulsifier is a complex emulsifying system of cationic emulsifier and non-ionic emulsifier, and the shell monomer mixture contains acrylate monomers and glycidyl methacrylate monomers; third step, preparing an initiator aqueous solution; fourth step, seed emulsion reaction and core layer polymerization: water, emulsifier, and part of the core monomer pre-emulsion as seed emulsion are added to the reaction kettle, and part of the initiator solution is added for initialization reaction; then the remaining core monomer pre-emulsion and part of the initiator solution are added dropwise for core layer emulsion polymerization; fifth step, shell layer polymerization: the shell monomer pre-emulsion and the remaining initiator solution are added dropwise to the core layer emulsion obtained in the fourth step for shell layer emulsion polymerization, to obtain an epoxy-functionalized polyacrylate polymer microsphere water dispersion with core-shell structure.